Really a nontraded commodity? A look at the international potato trade network (dataset and R code) - Kleinwechter, U.; Suarez V (2013)
This archive contains code and data for a social network analysis of international potato trade that was published at https://perspectivesandforesight.wordpress.com/2012/11/08/really-a-nontraded-commodity-a-look-at-the-international-potato-trade-network/ on 08 November, 2012. It can serve as a reference for understanding the analysis, and as a basis for replication of the results as well as for carrying out more detailed analyses of international potato trade. The following information and data is included: - The R code used for the social network analysis of international potato trade. - Data files with bilateral matrices of global trade in fresh, frozen and seed potatoes. - Data files with supplementary data used for the analysis. - A copy of the original blog post that was written using the data and code provided herewith.